How flavor works : the science of taste and aroma - Choi, Nak-Eon, 1965- (John Wiley & Sons Inc., 2015)
Taste is the number one driving force in the decision to purchase a food product and food consumption is the most critical function for living organisms to obtain the energy and resources essential to their vitality. Flavor and aroma are therefore universally important concepts: intrinsic to human well-being and pleasure, and of huge significance for the multi-trillion dollar global food business. How Flavor Works: the Science of Taste and Aroma offers a fascinating and accessible primer on the concepts of flavor science for all who have an interest in food and related topics. Professionals.